Effect of Gamification on Teaching-Learning Process: A Descriptive Study - Bose, Boney; Philip, Yohan; Joseph, Ajay; Abraham, Mathew (Indian Journal of Educational Technology, 2024)
Nowadays, education is going through a moment of methodological transformation. One of the active methodologies with excellent projection within the educational field is gamification. However, there is still a lack of awareness among educators about the acceptable implementation of the technique of gamification. This study analysed the effect of the gamification approach in teaching and learning, which covers students’ benefits, especially understanding level, engagement level, motivating factor, the significance of gamification as an assessment tool and also the barriers to using gamification. The research design was descriptive research with a sample of 509 from two developing and academically advancing countries, India and Malaysia, which includes teachers, research scholars, and students. Data is being collected with a questionnaire. The study findings reveal that gamiﬁcation can be a useful tool for teaching and learning and can increase learner’s motivation and turn learning into an enjoyable process. We also find that gamified learning interventions have a positive impact on student learning. These findings will be of practical interest to teaching and learning practitioners working in a range of educational contexts; and at all levels of education; who wish to increase student engagement and enhance learning. The study also finds that gamification still has some barriers to implementation and acceptance all around, especially among age groups above 50.